KEANEKARAGAMAN JENIS JAMUR DI TAMAN WISATA ALAM SITUGUNUNG, CISAAT, SUKABUMI - - Triastinurmiatiningsih; Tri Saptari Haryani; Jureka Tampubolon (Universitas Pakuan, 2017)
Some of the various flora that Indonesia has is the diversity of fungi, lichens and moss. Taman natural Â tourism Situgunung is one place that is suitable for mushrooms. The study was conducted at an altitude of 950 m above sea level, 990 m above sea level and 1050 m above sea level. Each height is made of three transect lines with a length of each 100 m transect with a total plot of 90 plot samples. Each transect is made of 10 sample plots measuring 1 x 1 m with a spacing between 10 m. The important value index (INP) that dominates each height is Marasmius copelandi, the height of 990 m above sea level is Stereum ostrea, and the Important Value Index at an altitude of 1050 is Stereum sp. Diversity index of fungal species in the TWA Situgunung area is high with an average value of 3.78.Key words : Situgunung, fungi, index diversity